Efficient domain decomposition based reliability analysis for polymorphic uncertain material parameters. Issue 1 (14th December 2021) - Schmidt, Albrecht; Lahmer, Tom
Abstract: Realistic uncertainty description incorporating aleatoric and epistemic uncertainties can be described within the framework of polymorphic uncertainty, which is computationally demanding. Utilizing a domain decomposition approach for random field based uncertainty models the proposed level‐based sampling method can reduce these computational costs significantly and shows good agreement with a standard sampling technique. While 2‐level configurations tend to get unstable with decreasing sampling density 3‐level setups show encouraging results for the investigated reliability analysis of a structural unit square.